A Surprising Role for the Sch9 Protein Kinase in Chromosome Segregation in Candida albicans. Issue 3 (15th January 2015) - Varshney, Neha; Schaekel, Alida; Singha, Rima; Chakraborty, Tanmoy; van Wijlick, Lasse; Ernst, Joachim F; Sanyal, Kaustuv
Abstract: The AGC kinase Sch9 regulates filamentation in Candida albicans . Here, we show that Sch9 binding is most enriched at the centromeres in C. albicans, but not in Saccharomyces cerevisiae . Deletion of CaSch9 leads to a 150- to 750-fold increase in chromosome loss. Thus, we report a previously unknown role of Sch9 in chromosome segregation.